Materiality in Financial Reporting. - Bellandi, Francesco (Emerald Publishing Limited, 2017)
This book offers an integrated perspective of materiality from the different angles of accounting, auditing, internal controls, management commentary, financial analysis, management control, forensic analysis, sustainability reporting, corporate responsibility, assurance standards, integrated reporting, and limited legal considerations.